2015
DOI: 10.1103/physrevd.91.053008
|View full text |Cite
|
Sign up to set email alerts
|

Higgs inflation from standard model criticality

Abstract: The observed Higgs mass MH = 125.9 ± 0.4 GeV leads to the criticality of the standard model, that is, the Higgs potential becomes flat around the scale 1017-18 GeV for the top mass 171.3 GeV. Earlier we proposed a Higgs inflation scenario in which this criticality plays a crucial role. In this paper, we investigate the detailed cosmological predictions of this scenario in light of the latest Planck and BICEP2 results. We also consider the Higgs portal scalar dark matter model, and compute the Higgs one-loop ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
168
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(178 citation statements)
references
References 131 publications
9
168
0
Order By: Relevance
“…The model is rewritten as renormalization-group corrected gauge-Higgs-Yukawa Lagrangian with compositeness conditions. In this way, this looks qualitatively similar to the study of RG improved effective potential in curved spacetime (Elizalde and Odintsov 1993, 1994a, 1994b and corresponding RG improved inflation (Simone et al 2009;Mukaigawa et al 1998;Lee 2013;Okada and Shafi 2013;Barenboim et al 2014;Hamada et al 2014aHamada et al , 2014bHamada et al , 2015Woodard 2008;Oda and Tomoyose 2014;Ren et al 2014;Inagaki et al 2014Inagaki et al , 2015Elizalde et al 2014;He and Xianyu 2014;Herranen et al 2014Herranen et al , 2015. In Sect.…”
Section: Introductionsupporting
confidence: 57%
“…The model is rewritten as renormalization-group corrected gauge-Higgs-Yukawa Lagrangian with compositeness conditions. In this way, this looks qualitatively similar to the study of RG improved effective potential in curved spacetime (Elizalde and Odintsov 1993, 1994a, 1994b and corresponding RG improved inflation (Simone et al 2009;Mukaigawa et al 1998;Lee 2013;Okada and Shafi 2013;Barenboim et al 2014;Hamada et al 2014aHamada et al , 2014bHamada et al , 2015Woodard 2008;Oda and Tomoyose 2014;Ren et al 2014;Inagaki et al 2014Inagaki et al , 2015Elizalde et al 2014;He and Xianyu 2014;Herranen et al 2014Herranen et al , 2015. In Sect.…”
Section: Introductionsupporting
confidence: 57%
“…It is observed that the two-loop contribution is softened for μ 2 = φ 2 N . It should be noted that we can tune the couplings, λ 0 and ξ 0 consistent with the current observational constraints for n s and r. In SM Higgs inflation the quartic coupling vanishes near the Planck scale [24]. A small positive value of the non-minimal scalar curvature coupling is favored for a simple scalar quadratic potential [35].…”
Section: Discussionmentioning
confidence: 73%
“…Quantum field theory in curved spacetime induces log terms in the scalar four-point as well as in http the non-minimal scalar-curvature sector, for the corresponding effective potential [12,13]. The account of such quantum-corrected terms in the potential, especially RG improved effective potential, is done for the study of inflation in [14][15][16][17][18][19][20][21][22][23][24][25][26]. It is also interesting to note that the reconstruction of the inflationary scalar potential as is done in [27] maybe applied to such non-minimal inflationary scalar potential.…”
Section: Introductionmentioning
confidence: 99%
“…r 0.003. The announcement of BICEP2 for B-mode detection [3] with a large value r 0.2 motivated people to make some efforts to reconcile Higgs inflation with the BICEP2 results [16][17][18][19]. Soon, it turned out that there is serious doubt about the BICET2 results [4,5].…”
Section: Introductionmentioning
confidence: 99%